2015
DOI: 10.1111/jsm.13022
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Functions and Clinical Characterization of Patients with Gender Dysphoria (GD) Undergoing Sex Reassignment Surgery (SRS)

Abstract: Introduction Cross-sex hormone treatment of gender dysphoria (GD) patients changing from male to female a prerequisite for sex reassignment. For initial physical adaptation, a combined treatment of anti-androgens and estrogens is used. Provided that patients fulfill specific criteria, sex reassignment surgery (SRS) presents the final step toward physical adaptation. However, systematic studies analyzing effects of hormone treatment regimens are lacking. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
64
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 29 publications
(38 reference statements)
5
64
2
3
Order By: Relevance
“…Ultrastructural studies showed a loss of the apico-basal differentiation in Sertoli cells and dedifferentiation of Leydig cells after estrogen treatment3940. However, detailed histomorphological and histochemical analyses of the effects of long-term treatment with estradiol, specifically linked to a patients‘ treatment plans are still lacking, as stated in the literature41.…”
mentioning
confidence: 99%
“…Ultrastructural studies showed a loss of the apico-basal differentiation in Sertoli cells and dedifferentiation of Leydig cells after estrogen treatment3940. However, detailed histomorphological and histochemical analyses of the effects of long-term treatment with estradiol, specifically linked to a patients‘ treatment plans are still lacking, as stated in the literature41.…”
mentioning
confidence: 99%
“…How long CHT should be provided before SRS is a matter of debate. We performed a multi‐center study revealing that some clinics advise their patients to terminate CHT several weeks prior to SRS, whereas other clinics advise continued treatment until the day of surgery (Schneider et al ., ). Reasons for discontinuation of CHT include the fear of increased bleeding during surgery or complications of wound healing in post‐operative care (Hess et al ., ).…”
Section: Cross‐sex Hormone Therapy (Cht)mentioning
confidence: 97%
“…In our study, we found a highly diverse outcome: More feminized hormonal levels (low testosterone, high estradiol levels) on the day of SRS were seen with continued CHT. In contrast, termination of CHT days or weeks prior to SRS leads to a partial or full masculine hormone profile (Schneider et al ., ). Several questions remain unanswered: Do different male or female hormone patterns on the day of SRS have any implications for the well‐being of the individual patient prior or post‐surgery?…”
Section: Cross‐sex Hormone Therapy (Cht)mentioning
confidence: 97%
See 2 more Smart Citations